IMPACT OF HUMAN CAPITAL AND ENTREPRENEURIAL LEADERSHIP STYLE ON THE ORGANIZATIONAL PERFORMANCE OF TABLE WATER ENTERPRISES IN MINNA, NIGER STATE - Ahmed ABDULKAZEEM; Modupe Mercy ADEYEYE (Malete Journal of Accounting and Finance, 2024)
Organizational performance depends on two key elements, human capital and entrepreneurial leadership style, a combination that has sparked interest among researchers and practitioners. Based on these facts, this study investigates the impact of human capital and entrepreneurial leadership styles on organizational performance. A cross-sectional survey design was adopted for the study and data was elicited through questionnaire. Research objectives and research questions were set and the targeted population comprised of six hundred fifty-eight (658) workers from Table Water Enterprises in Minna, Niger State while the sample size is one hundred and ninety-two (192). IBM SPSS 24.0 was used to analyze data. Regression, reliability analysis, and descriptive statistics were used. Human capital, entrepreneurial leadership style is assumed to account for 39.1% of the variability in other variables (R2 of 0.391), and the independent factors statistically substantially predict the dependent variable, F 60.710, p <.0005. The unstandardized coefficient for human capital, B1, equals 0.317, while entrepreneurial leadership style equals 0.406. This indicates 0.317 and 406 increases in organization performance for every increase in human capital and entrepreneurial leadership style. The study concludes that human capital positively impacts organizational performance through training, skills, competence, experience and innovation initiatives. It strengthens organizational performance when the entrepreneurial leadership style is high. The study recommends that organizations should invest in human capital development to enhance the knowledge, skills, and experience of their employees. And that entrepreneurial leadership style should be encouraged and developed through training programs, mentoring, and leadership development initiatives.